2015
DOI: 10.2217/bmm.15.97
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Oncogenes Identified by Microarray and RNA-Sequencing as Biomarkers for Clinical Prognosis

Abstract: The highly consistency of DEGs in their regulation directionality and molecular functions indicated the good reproducibility between microarray and RNA-sequencing in identifying potential oncogenes for clinical prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…With the development of human gene sequencing technology, high-throughput gene expression profiles have been widely used to detect the biomarkers of human diseases, which provides a chance to explore effective indicators for guiding the diagnosis, treatment and evaluating the prognosis of ovarian cancer [15,16]. In recent years, database-based bioinformatic analysis of expression profile has been widely applied to screen out target biomarkers of diagnostic and prognostic value [17].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of human gene sequencing technology, high-throughput gene expression profiles have been widely used to detect the biomarkers of human diseases, which provides a chance to explore effective indicators for guiding the diagnosis, treatment and evaluating the prognosis of ovarian cancer [15,16]. In recent years, database-based bioinformatic analysis of expression profile has been widely applied to screen out target biomarkers of diagnostic and prognostic value [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to explore new melanoma markers to guide the clinical treatment and improve melanoma prognosis. Gene-based biomarkers have become more popular with the advances in human gene sequencing [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown a tightly association between miRNAs and the pathogenesis of pterygium [6, 1519]. Nowadays, high-throughput platform has become a mainstream method to identify general RNA (including noncoding RNA) alteration [20, 21]. Because of bioinformatics' information integration ability, it is conducive to get new direction effectively.…”
Section: Introductionmentioning
confidence: 99%